In situ preparation of crosslinked polymer electrolytes for lithium ion batteries: A comparison of monomer systems - Roechow, Eike T.; Coeler, Matthias; Pospiech, Doris; Kobsch, Oliver; Mechtaeva, Elizaveta; Vogel, Roland; Voit, Brigitte; Nikolowski, Kristian; Wolter, Mareike (Polymers, 2020)
Solid polymer electrolytes for bipolar lithiumion batteries requiring electrochemical stability of 4.5 V vs. Li/Li+ are presented. Thus, imidazolium-containing poly(ionic liquid) (PIL) networks were prepared by crosslinking UV-photopolymerization in an in situ approach (i.e., to allow preparation directly on the electrodes used). The crosslinks in the network improve the mechanical stability of the samples, as indicated by the free-standing nature of the materials and temperature-dependent rheology measurements. The averaged mesh size calculated from rheologoical measurements varied between 1.66 nm with 10 mol% crosslinker and 4.35 nm without crosslinker. The chemical structure of the ionic liquid (IL) monomers in the network was varied to achieve the highest possible ionic conductivity. The systematic variation in three series with a number of new IL monomers offers a direct comparison of samples obtained under comparable conditions. The ionic conductivity of generation II and III PIL networks was improved by three orders of magnitude, to the range of 7.1 × 10-6 S·cm-1 at 20 °C and 2.3 × 10-4 S·cm-1 at 80 °C, compared to known poly(vinylimidazolium·TFSI) materials (generation I). The transition from linear homopolymers to networks reduces the ionic conductivity by about one order of magnitude, but allows free-standing films instead of sticky materials. The PIL networks have a much higher voltage stability than PEO with the same amount and type of conducting salt, lithium bis(trifluoromethane sulfonyl)imide (LiTFSI). GII-PIL networks are electrochemically stable up to a potential of 4.7 V vs. Li/Li+, which is crucial for a potential application as a solid electrolyte. Cycling (cyclovoltammetry and lithium plating-stripping) experiments revealed that it is possible to conduct lithium ions through the GII-polymer networks at low currents. We concluded that the synthesized PIL networks represent suitable candidates for solid-state electrolytes in lithium ion batteries or solid-state batteries.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Electrochemical stability; Ionic conductivity; Lithium ion battery; Photopolymerization; Polymer electrolyte; Polymeric ionic liquid